2009
DOI: 10.1080/03009740802448833
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the assessment of metacarpophalangeal joint disease in early psoriatic and rheumatoid arthritis

Abstract: Although conventional MRI shows evidence of an enthesitis-associated pathology in the MCP joints in PsA, this is not sufficiently common to be of diagnostic utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 21 publications
3
30
0
1
Order By: Relevance
“…McGonagle et al ,17 based on the finding of prominent bone marrow oedema at ligamentous attachments, proposed PsA should be considered an entheseal-based disease with secondary involvement of synovial structures. Subsequent studies confirmed the marrow oedema but showed it is non-PsA-specific and found in only a proportion of PsA patients 18. The present study showing that a genotype containing B*27:05:02-C*01:02:01 more strongly predicts the development of enthesitis in PsA, whereas the B*08:01:01-C*07:01:01 haplotype and its alleles are conversely associated with more synovial-based pathology such as joint deformity and joint fusion, is more consistent with the latter report.…”
Section: Discussionmentioning
confidence: 99%
“…McGonagle et al ,17 based on the finding of prominent bone marrow oedema at ligamentous attachments, proposed PsA should be considered an entheseal-based disease with secondary involvement of synovial structures. Subsequent studies confirmed the marrow oedema but showed it is non-PsA-specific and found in only a proportion of PsA patients 18. The present study showing that a genotype containing B*27:05:02-C*01:02:01 more strongly predicts the development of enthesitis in PsA, whereas the B*08:01:01-C*07:01:01 haplotype and its alleles are conversely associated with more synovial-based pathology such as joint deformity and joint fusion, is more consistent with the latter report.…”
Section: Discussionmentioning
confidence: 99%
“…For obvious ethical reasons, there was no histologic gold standard, so, like other investigators, we used the MRI as the gold standard. It is theoretically possible that contrast-enhanced MRI may lack specificity; indeed, studies of the pediatric wrist and adult sacroiliac joint have shown abnormalities in sizeable proportions of healthy control subjects 32,33 . As discussed, however, TMJ fluid and enhancement appear to be rare findings in children without JIA 14 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…However, how should we classify the patient with psoriasis and arthritis not in the distal interphalangeal joints but only in more proximal hand joints? Should the decision depend on the severity of the skin psoriasis or possibly on imaging evidence of involvement of the entheses?16…”
Section: Methodological Mattersmentioning
confidence: 99%